The modern novel : a short introduction - Matz, Jesse (Malden, MA : Blackwell Pub., 2004)
This book introduces readers to the history of the novel in the the nineteenth century and demonstrates its ongoing relevance as a literary form.
When and Why: The Rise of the Modern Novel -- The "New Novel," circa 1914 -- Seven Modern Novelists -- "What is Reality?": The New Questions -- New Forms: Reshaping the Novel -- New Difficulties -- Regarding the Real World: Politics -- Questioning the Modern: Mid-Century Revisions -- Postmodern Replenishments -- Postcolonial Modernity -- Conclusions: Four Contemporary Modern Novelists -- The Future of the Modern Novel.
Includes bibliographical references (p. 182-189) and index.
Keywords: English fiction -- 20th century -- History and criticism; Modernism (Literature) -- English-speaking countries; American fiction -- 20th century -- History and criticism